Data disaster recovery model for the association of bureaux de change operators of Nigera, Abcon Nigeria - Abubakar Magira Tom, 1988-, author; Norafida Ithnin, supervisor; Fakulti Komputeran (2015)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2015